El Icaromenipo de Luciano de Samósata: la risa, entre el spoudogeloîon y la carnavalesca de Bajtin - Cabrero, María del Carmen (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2010)
By mid-second century of our age, Lucian of Samosata, in a state of ‘Menippean fervour’ produced a series of plays starred by one of his favorite alter ego: Menippus, a literary shadow acclaimed by the personality —allegedly historical— of the cynic philosopher Menippus of Gadara. We are then in the presence of the nature of the spoudogeloîon genre. However, since Lucian would probably be reluctant to such limitation, in the article we will promote its interpretation in terms of menippean satire or carnivalesque, formulated by the Russian Bajtin a half-century ago and more recently reworked by authors such as Wolgang Rösler or Alberto Camerotto; it is our desire, amongst such an intermediation, not to lose the joyful sensation that a first reading of the Icaromenipo produces in the reader.
Keywords: Spoudogeloîon genre; Menippean satire; Imaginary voyage